The High Energy Solar Corona: Waves, Eruptions, Particles 2007
DOI: 10.1007/978-3-540-71570-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Complexity, Fragmentation, Particle Acceleration and Radio Emission from the Sun

Abstract: Abstract. The most popular flare model used to explain the energy release, particle acceleration and radio emission is based on the following assumptions: (1) The formation of a current sheet above a magnetic loop, (2) The stochastic acceleration of particles in the current sheet at the helmet of the loop, (3) the transport and trapping of particles inside the flaring loop. We review the observational consequences of the above model and try to generalize by putting forward a new suggestion, namely assuming tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Cascading fragmentation of the current layer is closely related to another puzzling question of current solar flare research -the apparent contradiction between observed regular large-scale dynamics and signatures of fragmented energy release in (eruptive) flares. This duality is reflected by two classes of flare models: The 'classical' CSHKP scenario based on magnetic reconnection in a single global flare current sheet and the class of "self-organized criticality" (SOC) models based on the avalanche of small-scale reconnection events in multiple current sheets formed as a consequence of either chaotic (Aschwanden 2002;Vlahos 2007) or regular but still complex boundary motions causing, e.g., magnetic braiding (Wilmot-Smith et al 2010).…”
Section: Fragmented Energy Release and Particle Accelerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cascading fragmentation of the current layer is closely related to another puzzling question of current solar flare research -the apparent contradiction between observed regular large-scale dynamics and signatures of fragmented energy release in (eruptive) flares. This duality is reflected by two classes of flare models: The 'classical' CSHKP scenario based on magnetic reconnection in a single global flare current sheet and the class of "self-organized criticality" (SOC) models based on the avalanche of small-scale reconnection events in multiple current sheets formed as a consequence of either chaotic (Aschwanden 2002;Vlahos 2007) or regular but still complex boundary motions causing, e.g., magnetic braiding (Wilmot-Smith et al 2010).…”
Section: Fragmented Energy Release and Particle Accelerationmentioning
confidence: 99%
“…Because of these difficulties an alternative concept based on the so-called "self-organized criticality" (SOC) has been proposed (Aschwanden 2002;Vlahos 2007). This class of models is based on the idea of multiple small-scale CSs embedded in chaotic (braided) magnetic fields that are formed as a consequence of random motions at the system boundary (photosphere).…”
Section: Introductionmentioning
confidence: 99%
“…Standard scenarios with a single dissipative region suffer by the insufficient volume for acceleration of the huge number of particles inferred from HXR observations (e.g. Vlahos, 2007). Because many dissipation regions separates multiple plasmoids in the small-scale regime of reconnection the total volume of all dissipation regions is much larger, allowing for possible reconciliation between observed and modelled fluxes of energetic particles.…”
Section: Introductionmentioning
confidence: 98%
“…Various mechanisms for producing these high-energy particles have been proposed [2,32,37], including wave-particle interactions, turbulence and collapsing magnetic traps: but a convincing idea is that the strong super-Dreicer electric fields, intrinsic to magnetic reconnection, directly accelerate charged particles. In the 'standard flare model', the acceleration site is located in a current sheet above the flare loops, and high-energy particles propagate down to the dense chromosphere where they slow down, emitting bremsstrahlung.…”
Section: Introductionmentioning
confidence: 99%